GA document 121 :. (Tokyo : A.D.A. edita, 2011)
- AZL/Zhang Lei: Nanjing University Staff Club, Nanjing, China##- Alejandro Aravena: Municipal Theatre of Constitucion, Constitucion, Maule, Chile##- BIG/Bjarke Ingels: West 57th Street, Manhattan, New York, U.S.A.##- Inaqui Carnicero: Sculptures Museum in Leganes, Leganes, Spain##- Delugan Meissl Associated Architects: Festival Hall of the Tiroler Festspiele Erl, Erl, Tyrol, Austria##- Sou Fujimoto: Beton Hala Waterfront Center, Belgrade, Serbia##- Anton Garcia-Abril: Reader's House -Madrid's Old Slaughterhouse, Arganzuela, Madrid, Spain##- Grupo SP: Housing at Itacolomi Street, Sao Paulo, SP, Brazil##- Christian Kerez: University of Applied Sciences and Arts, Muttenz, Muttenz, Switzerland##- Kengo Kuma: Progetto Manifattura -Green Innovation Factory, Rovereto, Trento, Italy##- Michael Maltzan: St. Petersburg Pier, St. Peterburg, Florida, U.S.A.##- Mansilla + Tunon: Royal Collections Museum, Palacio Real, Madrid, Spain##- MVRDV: ROCKmagneten, Roskilde, Denmark##- Hrvoje Njiric: Za_breg 2012, Zagreb, Croatia##- O'Donnell + Tuomey: Central European University Campus Development, Budapest, Hungary##- Smiljan Radic: Regional Theatre of Bio Bio, Concepcion, Region of Bio Bio, Chile##- Michel Rojkind: Cineteca Nacional del Siglo XXI, Mexico City, Mexico##- SANAA: Grace Farms Project, New Canaan, Connecticut, U.S.A.##- Selgascano: Yenikapi Transfer Point & Archaeo-Park Area , Istanbul, Turkey##- Fran Silvestre : Eolica -Wind Tower , Valencia, Spain##- Snohetta: Guadalajara Museum of Environmental Sciences, Guadalajara, Jalisco, Mexico##- SPBR arquitetos: Casa Pico, Lugano, Switzerland##- Studio 8/CJ Lim: Downtown Fargo Urban-Infill, North Dakota, U.S.A.##- Wolfgang Tschapeller: Angewandte_NEU -University of Applied Arts Vienna, Vienna, Austria##- UNStudio: King David the Builder International Airport, Kutaisi, Georgia##- Urbanus: Artron Art Center, Shenzhen, China##- Wang Shu: Tiles Hill -New Reception Center in Xiangshan
boek